2020
DOI: 10.1186/s40814-020-00661-7
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin insert dinoprostone versus trans-cervical balloon catheter for outpatient labour induction: a randomised controlled trial of feasibility (PROBIT-F)

Abstract: Background: The aim was to assess the feasibility of conducting a randomised controlled trial (RCT) of induction of labour comparing use of two methods in the outpatient setting. Methods: An open-label feasibility RCT was conducted in two UK maternity units from October 2017 to March 2019. Women aged ≥ 16 years, undergoing induction of labour (IOL) at term, with intact membranes and deemed suitable for outpatient IOL according to local guidelines were considered eligible. They were randomised to cervical ripen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…It is worth noting, however, that in none of the studies found the obstetric results in the group of MVI-induced patients were worse than in the DVI 9 , 14 , 15 , 17 , which also applies to patients with hypertensive disorders of pregnancy 18 and patients who experienced adverse events after using MVI or DVI 10 , although in this last case the cited analysis seems to have too little statistical power to detect differences. Relatively high safety of DVI results in attempts to use it in an outpatient setting 19 , combining it with mechanical pre-induction using a Foley catheter 20 and in patients after CS 21 . An undoubted advantage of MVI is the registration for use during pregnancy from 36 weeks and in the case of the rupture of the membranes.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting, however, that in none of the studies found the obstetric results in the group of MVI-induced patients were worse than in the DVI 9 , 14 , 15 , 17 , which also applies to patients with hypertensive disorders of pregnancy 18 and patients who experienced adverse events after using MVI or DVI 10 , although in this last case the cited analysis seems to have too little statistical power to detect differences. Relatively high safety of DVI results in attempts to use it in an outpatient setting 19 , combining it with mechanical pre-induction using a Foley catheter 20 and in patients after CS 21 . An undoubted advantage of MVI is the registration for use during pregnancy from 36 weeks and in the case of the rupture of the membranes.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, 71.9% of the women with IOL received outpatient care. Other studies on outpatient IOL using other IOL methods report proportions of eligible women ranging from 8.3% to 53.0% 21–23 . Although eligibility criteria for outpatient IOL are not described in detail in all the papers, the published criteria seem comparable to the LINO study criteria, with some differences regarding women with hypertension, preeclampsia, diabetes, and small‐for‐gestational‐age fetuses.…”
Section: Discussionmentioning
confidence: 99%
“…With the ongoing COVID-19 pandemic, there is an additional incentive to reduce the burden on hospital resourcesand to safely keep patients out of the hospital. Furthermore, publishing on outpatient cervical ripening increased dramatically in 2020 showing a global increase in interest (7,8,16,(35)(36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%